ANALISIS PENGARUH BIAYA DANA (COST OF FUND) DAN RASIO LIKUIDITAS TERHADAP RENTABILITAS DENGAN MENGGUNAKAN PENDAPATAN BUNGA SEBAGAI VARIABEL INTERVENING (Studi kasus PT. Bank Bukopin, (Persero) Tbk Cabang Kediri Periode Agustus 2014 – April 2017) - Hesti Hesti; Eka Askafi (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
The purpose of this study is analyze the direct and indirect effects of cost demand deposit funds, cost of savings funds, cost of deposit funds and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) by using Net Interest Margin (NIM) as intervening variable. The method of analysis in this study is Path Analysis. The data is obtained from the budget realization report of Financial Planning and Accounting Division of Bank Bukopin period August 2014 until April 2017. The results showed that with 5% significance level, only cost of savings funds and LDR had direct influence on NIM and ROA, and NIM as intervening variable had significant effect on ROA with determination coefficient value () of 93.6%. NIM as an intervening variable of this study mediates the effect of LDR on ROA, but does not mediate the effect of cost of savings funds on ROA, so cost of savings funds have a direct effect on ROA without going through NIM.